2010
DOI: 10.3923/pjbs.2010.120.125
|View full text |Cite
|
Sign up to set email alerts
|

Breed and Seasonal Variations in the Testicular Morphometry, Gonadal and Extragonadal Sperm Reserves of the Barred Plymouth Rock and Nigerian Indigenous Breeds of the Domestic Fowl

Abstract: Breed and seasonal influence on testicular morphometry, Gonadal Sperm Reserves (GSR), Extragonadal Sperm Reserves (ESR) was investigated in the barred Plymouth rock and the Nigerian indigenous breeds of the domestic fowl. Twenty sexually matured birds per breed were studied in the four seasons of the year. Breed significantly (p<0.01) influenced the body weight (2.11 +/- 0.05 vs. 1.58 +/- 0.02), paired testes weight (21.92 +/- 1.46 vs. 12.43 +/- 0.91) and all other morphometric parameters with the barred Plymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 20 publications
1
11
0
1
Order By: Relevance
“…This deduction is supported by Adeyemo et al (2007) and Gbore and Egbunike (2008), who observed high correlations between testis weight, body weight, sperm production and testis sperm reserve potential. In line with this, Orlu and Egbunike (2010) also propounded that because testis weight is highly significantly (P<0.01) related to gonadal and extragonadal sperm reserves, daily sperm production, gonadal and extragonadal sperm reserves could be calculated from testicular weight. On the contrary, Orgebin-Crist (1968), Weisgold and Almquist (1979), and Wildeus and Entwistle (1982) reported no correlation between gonadal sperm reserves and body weight in rabbits.…”
Section: Resultsmentioning
confidence: 68%
“…This deduction is supported by Adeyemo et al (2007) and Gbore and Egbunike (2008), who observed high correlations between testis weight, body weight, sperm production and testis sperm reserve potential. In line with this, Orlu and Egbunike (2010) also propounded that because testis weight is highly significantly (P<0.01) related to gonadal and extragonadal sperm reserves, daily sperm production, gonadal and extragonadal sperm reserves could be calculated from testicular weight. On the contrary, Orgebin-Crist (1968), Weisgold and Almquist (1979), and Wildeus and Entwistle (1982) reported no correlation between gonadal sperm reserves and body weight in rabbits.…”
Section: Resultsmentioning
confidence: 68%
“…al., 2005). The growth and development of testicular organs in various species of farm animals has been well documented (Orlu and Egbunike, 2010;Osinowo et. al., 1981;Bitto and Egbunike, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, the growth and development of testicular organs in various species of farm animals has been well documented (Osinowo et al, 1981;Rekwot et al, 1987;Etches, 1996;Oyeyemi & Ubiogoro, 2005;Bitto & Egbunike, 2006;Togun & Egbunike, 2006;Obidi et al, 2008;Ugwu, 2009;Orlu & Egbunike, 2010). Osinowo et al (1981) and Togun & Egbunike reported that testes size is a good indicator of the present and future sperm production in animals.…”
Section: Introductionmentioning
confidence: 99%